Plane Dependent Subject-Specific Neuromuscular Training for Knee Rehabilitation - Lee, Song Joo; Ren, Yupeng; Chang, Alison H.; Press, Joel M.; Hochberg, Marc C.; Zhang, Li-Qun (Institute of Electrical and Electronics Engineers, 2020)
Knee injuries at risk of post-traumatic knee osteoarthritis (PTOA) and knee osteoarthritis (OA) are closely associated with knee transverse plane and/or frontal plane instability and excessive loading. However, most existing training and rehabilitation devices involve mainly movements in the sagittal plane. An offaxis elliptical training system was developed to train and evaluate neuromuscular control about the off-axes (knee varus/valgus and tibial rotation) as well as the main flexion/extension axis (sagittal movements). Effects of the offaxis elliptical training system in improving either transverse or frontal neuromuscular control depending on subjects' need (Pivoting group, Sliding group) were demonstrated through 6-week subject-specific neuromuscular training in subjects with knee injuries at risk of PTOA or medial knee osteoarthritis. The combined pivoting and sliding group, named as offxis group demonstrated significant reduction in pivoting instability, minimum pivoting angle, and sliding instability. The pivoting group showed more reduction in pivoting instability, maximum and minimum pivoting angle than the sliding group. On the other hand, the sliding group showed more reduction in sliding instability, maximum and minimum sliding distance than the pivoting group. Based on these findings, the offaxis elliptical trainer system can potentially be used as a therapeutic and research tool to train human subjects for plane-dependent improvements in their neuromuscular control during functional weight-bearing stepping movements.